2020
DOI: 10.5327/z1679443520200425
|View full text |Cite
|
Sign up to set email alerts
|

Workplace violence among municipal health care workers in Diamantina, Minas Gerais, Brazil, 2017

Abstract: Background: Health care workers stand out in recent studies as a function of high rates of workplace violence. Objective: To calculate the prevalence of workplace violence involving health care workers and associated factors. Methods: Cross-sectional study with municipal health care workers in Diamantina, Minas Gerais, Brazil. Data were collected in interviews from December 2016 through March 2017. Variable workplace violence was considered as outcome on univariate and multivariate analysis. Descriptive and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 20 publications
0
7
0
5
Order By: Relevance
“…We noticed an association between psycho-verbal (9) and psycho-non-verbal (10). The violence practiced by people with professional relationships (12) occurred in the workplace (15), with emphasis on psycho-verbal violence (9). Aggressors identified as people with some personal connections (11) were responsible for non-verbal psychological (9) violence in public (16) and private ( 14) places, whereas the violence practiced by strangers (13) would occur in public places (16) (Fig 2).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We noticed an association between psycho-verbal (9) and psycho-non-verbal (10). The violence practiced by people with professional relationships (12) occurred in the workplace (15), with emphasis on psycho-verbal violence (9). Aggressors identified as people with some personal connections (11) were responsible for non-verbal psychological (9) violence in public (16) and private ( 14) places, whereas the violence practiced by strangers (13) would occur in public places (16) (Fig 2).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, conflicts can occur involving patients and/or their families [ 40 ]. Another study points to high workload as a factor that makes professionals less tolerant towards each other [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, efforts should be strengthened to prevent health care workers from being exposed to workplace violence. In some studies, female health care workers are significantly more likely to be exposed to workplace violence ( 47 , 48 ). But in this study, no statistically significant differences were found for sex which was consistent with previous research by Hahn et al ( 49 ).…”
Section: Discussionmentioning
confidence: 99%